Artemether, Artesunate, Arteannuin B, Echinatin, Licochalcone B and Andrographolide Effectively Inhibit SARS-CoV-2 and Related Viruses In Vitro - Hu, Yunjia; Liu, Meiqin; Qin, Hongbo; Lin, Haofeng; An, Xiaoping; Shi, Zhengli; Song, Lihua; Yang, Xinglou; Fan, Huahao; Tong, Yigang (Frontiers in Cellular and Infection Microbiology, 2021)
Since the first reported case caused by the novel coronavirus SARS-CoV-2 infection in Wuhan, COVID-19 has caused serious deaths and an ongoing global pandemic, and it is still raging in more than 200 countries and regions around the world and many new variants have appeared in the process of continuous transmission. In the early stage of the epidemic prevention and control and clinical treatment, traditional Chinese medicine played a huge role in China. Here, we screened out six monomer compounds, including artemether, artesunate, arteannuin B, echinatin, licochalcone B and andrographolide, with excellent anti-SARS-CoV-2 and anti-GX_P2V activity from Anti-COVID-19 Traditional Chinese Medicine Compound Library containing 389 monomer compounds extracted from traditional Chinese medicine prescriptions "three formulas and three drugs". Our discovery preliminary proved the stage of action of those compounds against SARS-CoV-2, and provided inspiration for further research and clinical applications.